Business Development Strategy With Balanced Method Scorecard (BSC) in Probolinggo Furniture Industrial Village - Wahdanatul Warida; Arnis Budi Susanto; Intan Nurul Awwaliyah (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This study aims to analyze the business development strategy implemented by the furniture industry community in Probolinggo using the balanced scorecard (BSC) method. The method used in this study is a qualitative descriptive analysis method by conducting interviews, observations, and data documentation in collecting the necessary data. Interviews were conducted on 12 informants consisting of 5 informants from business owners in Jorongan Village, Probolinggo, 3 informants from employees, and 4 from consumers. The results of the study based on the Balanced Scorecard through 4 measurement perspectives show that the financial perspective has decreased in ROI, current ratio , and operating ratio. The growth and learning perspective lacks training for employees and does not utilize technology in the form of social media in its marketing process. The company's readiness in implementing BSC must pay attention to the implementation of a BSC-based performance measurement system by first evaluating the suitability of the characteristics and readiness of the company in implementing BSC. Things that must be prepared are evaluating performance so that it can reflect activities in the company in accordance with the vision, mission, strategy, and objectives that have been set.